The relationship between nurses’ therapeutic communication and anxiety levels among patients receiving their first chemotherapy session: A cross-sectional study - Kiki Deniati; Lina Indrawati; Dinda Indrawati Bunga (Politeknik Negeri Subang, 2026)
Background: Patients receiving their first chemotherapy session often experience anxiety due to uncertainty about treatment procedures, side effects, and physical changes. Nurses' therapeutic communication is considered an essential intervention to provide emotional support and reduce anxiety. Purpose: This study investigated the relationship between nurses' therapeutic communication and anxiety in patients who received first chemotherapy session. Method: This quantitative cross-sectional study was conducted from August to December 2025. Seventy-five first-time chemotherapy patients were recruited using inclusion and exclusion criteria. Data were collected using a 10-item Therapeutic Communication Questionnaire and the Hamilton Anxiety Rating Scale (HARS). Univariate and bivariate analyses were performed using the Chi-square test at p < 0.05. Result: Among 75 patients completed the questionnaire, the findings showed that most respondents experienced high levels of therapeutic communication (76%) and had no anxiety (66.7%). The bivariate analysis demonstrated a significant correlation between therapeutic communication of nurses and anxiety levels among first chemotherapy session patients (p = 0.004). Conclusion: There is a significant relationship between nurses' therapeutic communication and anxiety in first-time chemotherapy patients. Effective therapeutic communication was associated with lower anxiety levels. Strengthening nurses' therapeutic communication skills may serve as an effective strategy to reduce anxiety and support nurse-led consultations prior to first treatment sessions.